ICVBCmobile: il laboratorio mobile dell'Istituto per la Conservazione e Valorizzazione dei Beni Culturali. Diagnostica, Monitoraggio, Conservazione e Valorizzazione integrata del patrimonio (Archeomatica, 2016)
ICVBC was founded in 2001 and is located in Florence with units in Rome and Milan.The institutional tasks of ICVBC include research, coordination, consultancyand training. ICVBC's features is its multidisciplinary character, promoting an interdisciplinary approach to research, guaranteed by different professionals, andthrough the development of an extensive national and international network ofcooperation with research institutes, universities and public or private subjectsinvolved in the conservation of Cultural Heritage.In the ï¬eld of conservation, various issues are addressed: study and development of materials for the conservation of stone, metallic artefacts and painted surfaces;development of diagnostic systems for identification and monitoring of theenvironmental parameters useful for the characterization of causes and mechanisms of decay; development of protocols for the conservation and scheduled maintenance; integrated enhancement and fruition of works of art and their urban context.Through the ICVBCmobile laboratory, the Institute provides diagnostics servicesusing portable equipment and non-destructive techniques, also offering consulting services for intervention design and restoration projects.